Constructability Research Trends: A Review and Future Directions - Sheng Ding, Chu; Salleh, Hafez; Ye Kho, Mei (International Journal of Sustainable Construction Engineering and Technology, 2020)
Implementing constructability concepts in a project can bring many benefits such as reduced project cost & duration, enhanced project quality, and improved site management. There were numerous research on constructability concepts since its introduction in late 1970. However, there are limited contemporary literature to review the research on constructability in a structured way. Therefore, this paper aims to review the literature with respective to the constructability concepts. The trend of constructability development, limitations of current research, research gaps and future direction will be briefly presented. Constructability development internationally will be discussed first before the limitation of the constructability research conducted in Malaysia are presented. The literature review reveals that the constructability research in Malaysia are still limited. Apart from building projects, there is a need for more constructability studies with respect to infrastructure projects. The trend of constructability development had moved towards the use of quantitative models. For future direction, quantitative models related to infrastructure projects in Malaysia can be developed. There is a potential of the quantitative models to be embedded with Building Information Modelling (BIM) so that automated assessment is made possible.